Synthesis and characterization of nanostructured ternary MAX-phase thin films prepared by magnetron sputtering as precursors for twodimensional MXenes - Miranda Marti, Marta (Pontificia Universidad Católica del Perú, 2023)
MAX phase thin films can be fabricated through firstly depositing a precursor thin film consisting of the initial elements M, A, and X close to the MAX phase stoichiometry employing physical vapor deposition techniques with a subsequent thermal annealing process. This work presents different deposition configurations (multilayer and co-sputtering) for the fabrication of the Ti2AlC and Ti3AlC2 MAX phase thin films by magnetron sputtering from three elemental targets (Ti, Al, and C). It was found that the depositions followed mainly amorphous thus the MAX phase was not able to form. By implementing the deposition parameters such as temperature and substrate voltage, the deposition morphology could be tailored to crystalline and MAX phases could be created. Moreover, Ti2AlC and Ti3AlC2 nanostructured MAX phase thin films were fabricated by magnetron sputtering with three elemental targets (Ti, Al, and C) at oblique angle, resulting in a columnar thin film, and the properties of the thin film were described as a function of the column tilt angle. Lastly, the MAX phases at normal configuration and at oblique angle configuration were wet etched and the properties of the resulting MXene thin films were analyzed. It was demonstrated that only the surface of the sample was attacked by the etching solution. Thus, only the surface of the MAX phase was transformed into MXene. This hypothesis was verified by multiple characterizations such as e.g., X-Ray Diffraction and Raman spectroscopy to understand the possible morphology and chemical transformation and its influence on the etched thin film properties. The aim of this work is to unravel the connection between the morphology of the MAX phase thin films and the properties of the resulting MXenes. By understanding this relationship, it would be possible to tailor their features for specific applications.

MAX-Phasen- Dünnschichten können hergestellt werden, indem zunächst eine Vorläufer- Dünnschicht mit den drei Elementen M, A und X nahe der Stöchiometrie der MAXPhasen durch physikalische Abscheidung aus der Gasphase abgeschieden wird, gefolgt von einem thermischen Glühprozess. In dieser Arbeit werden verschiedene Abscheidungskonfigurationen (Multilayer und Co-Sputtern) für die Herstellung von Ti2AlC und Ti3AlC2-MAX-Phasen-Dünnschichten durch Magnetron-Sputtern aus drei elementaren Targets (Ti, Al und C) vorgestellt. Es wurde festgestellt, dass die Abscheidungen hauptsächlich amorph erfolgten, so dass sich die MAX-Phase nicht bilden konnte. Durch Einstellen der Abscheidungsparameter wie Temperatur und Substratspannung konnte die Abscheidungsmorphologie auf kristalline beeinflusst werden. Darüber hinaus wurden Ti2AlC and Ti3AlC2 nanostrukturierte MAX-Phasen - Dünnschichten durch Magnetronsputtern mit drei elementaren Targets (Ti, Al und C) in einem schrägen Winkel hergestellt (Oblique Angle Deposition), was zu einer säulenförmigen Dünnschicht führte, und die Eigenschaften der Dünnschicht wurden als Funktion des Säulenwinkels beschrieben. Schließlich wurden die MAX-Phasen in normaler und OAD-Konfiguration geätzt und die Eigenschaften der resultierenden MXen-Dünnschichten analysiert. Es zeigte sich, dass nur die Oberfläche der Probe von der Ätzlösung angegriffen wurde. Somit wurde nur die Oberfläche der MAX-Phase in MXen umgewandelt. Diese Hypothese wurde durch verschiedene Untersuchungen wie Röntgenbeugung und Raman-Spektroskopie verifiziert, um die mögliche Morphologie und chemische Umwandlung und deren Einfluss auf die Eigenschaften der geätzten Dünnschicht zu verstehen. Ziel dieser Arbeit ist, den Zusammenhang zwischen der Morphologie der MAX-Phasen- Dünnschichten und den Eigenschaften der entstehenden MXene zu entschlüsseln. Durch das Verständnis dieses Zusammenhangs wäre es möglich, die Eigenschaften dieser Schichten für bestimmte Anwendungen zu optimieren.
Keywords: Películas delgadas; Espectrometría; Nanopartículas; https://purl.org/pe-repo/ocde/ford#2.00.00